TLR7 modulates extramedullary splenic erythropoiesis in P. yoelii NSM-infected mice through the regulation of iron metabolism of macrophages with IFN-γ - Li, Jiajie; Liu, Lin; Xing, Junmin; Chen, Dianhui; Fang, Chao; Mo, Feng; Gong, Yumei; Tan, Zhengrong; Liang, Guikuan; Xiao, Wei; Tang, Shanni; Wei, Haixia; et al. (Frontiers in Immunology, 2023)
Splenomegaly is a prominent clinical manifestation of malaria and the causes remain incompletely clear. Anemia is induced in malaria and extramedullary splenic erythropoiesis is compensation for the loss of erythrocytes. However, the regulation of extramedullary splenic erythropoiesis in malaria is unknown. An inflammatory response could facilitate extramedullary splenic erythropoiesis in the settings of infection and inflammation. Here, when mice were infected with rodent parasites, Plasmodium yoelii NSM, TLR7 expression in splenocytes was increased. To explore the roles of TLR7 in splenic erythropoiesis, we infected wild-type and TLR7-/- C57BL/6 mice with P. yoelii NSM and found that the development of splenic erythroid progenitor cells was impeded in TLR7-/- mice. Contrarily, the treatment of the TLR7 agonist, R848, promoted extramedullary splenic erythropoiesis in wild-type infected mice, which highlights the implication of TLR7 on splenic erythropoiesis. Then, we found that TLR7 promoted the production of IFN-γ that could enhance phagocytosis of infected erythrocytes by RAW264.7. After phagocytosis of infected erythrocytes, the iron metabolism of RAW264.7 was upregulated, evidenced by higher iron content and expression of Hmox1 and Slc40a1. Additionally, the neutralization of IFN-γ impeded the extramedullary splenic erythropoiesis modestly and reduced the iron accumulation in the spleen of infected mice. In conclusion, TLR7 promoted extramedullary splenic erythropoiesis in P. yoelii NSM-infected mice. TLR7 enhanced the production of IFN-γ, and IFN-γ promotes phagocytosis of infected erythrocytes and the iron metabolism of macrophages in vitro, which may be related to the regulation of extramedullary splenic erythropoiesis by TLR7.